The Problem of the Duties of the Committee Investigating Facts under the Constitution of the Kingdom of Thailand 2017: A Comparative Study of the Duties of Committees in the United States of America - Liengboonlertchai, Pornson (King Prajadhipok’s Institute Journal, 2025)
Due to the promulgation of the current Constitution, which includes provisions regarding the powers and duties of parliamentary committees that differ from those in the previous 2007 Constitution, there may be an impact on the effective performance of the legislative function. This research explores the investigative duties of committees under the structure of the Constitution of the Kingdom of Thailand 2017 through the framework of comparative constitutional law, focusing on the committee systems in the United States and Thailand. The research findings indicate that parliamentary committees face several problems, including overlapping roles, unclear authority in fact-finding duties, a lack of enforcement power to summon individuals for testimony or to require the submission of documents, and issues related to Article 129 of the Constitution, which imposes constraints on the committees' duties and affects the enforcement of the constitutional provisions outlined in Article 77. Therefore, Thailand needs to address these issues promptly by amending the Constitution, enacting new laws, and revising parliamentary rules based on the experiences of the United States to enhance the efficiency of parliamentary committees' performance.